1996
DOI: 10.1007/bf00021882
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of kernel modification found in South African quality protein maize inbred lines

Abstract: The genetic control of endosperm modification in 12 opaque-2 maize (Zea mays L.) inbred lines was investigated by means of a diallel cross experiment conducted across two environments. Kernel vitreousness and kernel hardness were determined by partially dominant genes. Additive gene action was largely responsible for kernel modification. A favourable general combining ability for kernel vitreousness and kernel hardness was positively correlated with an accumulation of dominant kernel modifying genes. South Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Vasal et al (1993aVasal et al ( , 1993b) studied kernel endosperm hardness while Pixley and Bjarnason (1993) studied protein concentration in grain, tryptophan concentration in grain, and tryptophan concentration in protein, which is similar to what is currently referred to as Quality Index in QPM breeding. Earlier research fi ndings on kernel endosperm-modifying factors also reported that the additive variance was more important than nonadditive variance (Bjarnason et al, 1976;Hohls et al, 1996; Table 6. General combining ability (GCA) effects of nine quality protein maize inbred lines for anthesis days and quality traits over seven and three environments, respectively.…”
Section: Combining Ability Effectsmentioning
confidence: 85%
“…Vasal et al (1993aVasal et al ( , 1993b) studied kernel endosperm hardness while Pixley and Bjarnason (1993) studied protein concentration in grain, tryptophan concentration in grain, and tryptophan concentration in protein, which is similar to what is currently referred to as Quality Index in QPM breeding. Earlier research fi ndings on kernel endosperm-modifying factors also reported that the additive variance was more important than nonadditive variance (Bjarnason et al, 1976;Hohls et al, 1996; Table 6. General combining ability (GCA) effects of nine quality protein maize inbred lines for anthesis days and quality traits over seven and three environments, respectively.…”
Section: Combining Ability Effectsmentioning
confidence: 85%
“…The use of the diallele crosses identified additive effects for hardness characteristics, with possible epistatic effects (91,103,120).…”
Section: Breedingmentioning
confidence: 99%
“…Significant variation among the genotypes for the traits indicated that allelic variations do occur. The significant variation for endosperm modification, protein and tryptophan contents in QPM inbreds and its crosses have been reported in several studies (Hohls et al 1996;Hossain et al 2008;Wattoo et al 2009;Hussain et al 2014 The 't' co-variances. The value of 'b' in case of protein content itself was close to zero rather than unity, however, in case of tryptophan content it was away from zero but due to high standard error in both the cases it showed non-significant departure from zero.…”
Section: Resultsmentioning
confidence: 78%